Canva-Based Folklore Transformation to Improve Students’ Poetry Writing Skills - Aisyah Sekar Sari; Yessi Fitriani; Puspa Indah Utami (Yayasan Sembilan Pemuda Indonesia, 2027)
This classroom action research examined how Canva-based folklore transformation improved senior high school students’ poetry writing skills. The study responded to students’ persistent difficulty in transforming narrative folklore into concise poetic expression, particularly in theme alignment, figurative language, diction, and atmosphere. Twenty-three tenth-grade students participated in two cycles of action research consisting of planning, implementation, observation, and reflection. Data were collected through poetry writing performance tests, observation sheets, and classroom documentation, then analyzed through descriptive-comparative procedures across the pre-action stage, Cycle I, and Cycle II. The intervention integrated selected folklore or hikayat texts, visual brainstorming, Canva-based poem design, teacher scaffolding, and peer sharing through digital links. The results showed a significant improvement. Classical mastery increased from 22% in the pre-action stage to 87% in Cycle I and 96% in Cycle II. The mean writing score also rose from 65.5 in the pre-action stage to 81.78 in Cycle I and 89.70 in Cycle II. The strongest gain appeared when visual scaffolding was combined with explicit guidance on figurative language and diction. This study contributes a practical model for connecting local folklore, visual digital media, and creative writing instruction. Its practical implication is that teachers can use Canva not only as a design tool but also as a structured creative space for planning, revising, publishing, and discussing literary texts.